AUDIT OF THE SELLING MANAGEMENT SYSTEM APPLICATION AT THE MAJU BERSAMA SHOP IN CIKANDE REGENCY. SERANG USING COBIT 5.0 - Purnama, Eris Dwi; Puspita, Yosi; Firmansyah, Dindin (JENTRE, 2024)
The Selling Management System application is an information system that helps manage sales data and sales reports at the Maju Bersama Cikande Store. In implementing the Selling Management System Application Information System, errors often occur due to input errors in inputting data. So it is necessary to carry out an Information System Audit. This research aims to assess the Capability Level and provide IT governance recommendations based on the COBIT 5.0 framework. So that you know what things need to be improved to achieve company goals. The research method used is qualitative by conducting interviews, observation and document study. The domains audited from the COBIT 5.0 mapping results are EDM02 (Ensure Benefit Delivery), APO10 (Manage Supplier), APO12 (Manage Risk), and DSS01 (Manage Operations). Based on the audited domain, the maturity value EDM02 was obtained with a value of 2,2, with a maturity level of 1 meaning the process had been implemented, APO10 with a value of 2.7, a maturity level of level 2 meaning the process had been recorded, measurable, and in accordance with the company's objectives, DSS01 with a value 1.5 with a maturity level of 1 and APO12 with a value of 1.41 with a maturity level of 1. Based on the findings of the EDM02 (Ensure Benefit Delivery) domain, the Selling Management System Application is required to improve application performance with regular updates and the addition of new application features, related to the findings of the DSS01 domain and APO12 is the need to back up the database, use a different user and password for each application user, and provide a generator set to mitigate the risk of power outages.